Properties of pain catastrophizing scale amongst patients with carpal tunnel syndrome - Item response theory analysis - Saltychev, Mikhail; Miikkulainen, Annika; Taskinen, Hanna-Stiina (WALTER DE GRUYTER GMBH, 2025)
Objectives To evaluate the psychometric properties of pain catastrophizing scale (PCS) using item response theory (IRT) amongst people with carpal tunnel syndrome (CTS).
Methods Retrospective cross-sectional register-based study amongst 1,597 patients with CTS. Two-parameter IRT analysis with rating scale model.
Results The average age was 55.3 (16.3) years and 896 (56%) were women. The average PCS total score was 15.1 (11.6) points. For all 13 items, the estimates of difficulty parameter indicated a shift towards higher PCS scores. This was also seen in item characteristic curves and item information function. Respectively, the entire composite score showed the same shift towards higher PCS scores. The discrimination of PCS was excellent 1.98 (95% CI 1.89-2.07).
Conclusions Overall, the psychometric properties of the PCS were found to be sufficiently good to recommend this scale for clinical use in CTS. The PCS is well able to distinguish between people with different levels of pain catastrophizing, even if performing better in elevated levels of catastrophizing. Also, the respondents may have a slight tendency to underestimate the severity of their catastrophizing when responding to the PCS. The results may be of interest to both clinicians and researchers in planning and implementing conservative or operative treatment for CTS, setting rehabilitation goals, and evaluating treatment or rehabilitation outcomes.